ANALISIS KINERJA PERUSAHAAN DAERAH AIR MINUM KOTA SAMARINDA (DITINJAU DARI ASPEK KEUANGAN) - Titin Ruliana, Mayosi Anggita, H. Eddy Soegiato K (EKONOMIA, 2015)
This study aims to determine the development of the Company's financial performance of City of Samarinda based on the Ministry of the Interior No. 47 of 1999 from the year 2011 to 2012. The analysis and hypothesis testing equipment used is quantitative method (the processing of data in the form of figures or numbers, which the results are compared with each other and found the final result). If the weight of financial performance PDAM Samarinda in 2012 higher than in 2011, the hypothesis is accepted and if the weight of financial performance PDAM Samarinda in 2012 was not higher than in 2011, the hypothesis is rejected. From the results of the study mentioned that the financial performance PDAM Samarinda in 2011 gained weight 26.25% and in 2012 gained the same weight is 26.25%. Then the hypothesis is rejected because of the weight of financial performance PDAM Samarinda in 2012 was not higher than in 2011.